Method for synchronous thinning forming and SEI coating modification of lithium-containing metal strip, modified lithium-containing metal strip and application of modified lithium-containing metal strip

By covering the halogen membrane on the surface of the lithium metal belt, a continuous, uniform and dense halogen lithium artificial SEI cover layer is formed during the processing process of the roller compression process, which solves the mechanical stability of lithium metal negative materials and battery assembly. The problem of poor sex and high production costs realizes the production of high -efficiency and low -cost lithium metal batteries.

CN119368557APending Publication Date: 2025-01-28SUZHOU RONGJU LITHIUM ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411512876.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, lithium metal negative electrode materials have problems such as poor mechanical stability, poor electrical contact, structural stress damage and high production costs during molding and battery assembly, and the manual SEI modification process is complex and costly.

Method used

By covering the halogen metroma membrane on the surface of the lithium metal belt, a continuous, uniform, and dense halimized lithium artificial SEI cover layer is formed during the roller compression processing process, and the synchronous thinning molding and SEI coverage of the lithium metal belt will be achieved. Essence

Benefits of technology

The efficient and low -cost production of lithium metal negative materials, improved the mechanical stability and electrochemical properties of materials, reduced production costs, and improved the consistency and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368557A_ABST
    Figure CN119368557A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-containing metal strip synchronous thinning forming and SEI coating modification method, a modified lithium-containing metal strip and application of the modified lithium-containing metal strip. The method comprises the following steps that S1, the surface of a roller is coated with a halogenated polymer film, and the roller with a halogenated polymer coating layer is obtained; and S2, rolling the lithium-containing surface of the lithium-containing metal belt by adopting a roller with a halogenated polymeric membrane coating layer, and forming an artificial SEI coating layer on the surface of the lithium-containing metal belt through SEI film forming reaction of the halogenated polymeric membrane coating layer and the lithium metal while thinning forming of the lithium-containing metal belt is realized. According to the invention, large-scale one-time processing forming of the flat lithium-containing metal belt coated with the artificial SEI on the surface can be realized, the product quality is high, the consistency is good, the method is more suitable for production of commercial battery electrode materials, and the performance consistency of commercial battery cells can be improved; in addition, the scheme provided by the invention can also be popularized to molding and modification of low-lithium / lithium-free negative electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage materials, and in particular to a method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification, a modified lithium-containing metal strip, and application of the modified lithium-containing metal strip as a negative electrode material in lithium metal primary / secondary batteries. Background Art

[0002] The commercial lithium-ion batteries currently used in the market are limited by the low capacity density (372mAh / g) of the graphite material used in their negative electrodes, making it difficult to achieve the national 2030 plan for high-capacity lithium batteries of 400-500Wh / kg. Therefore, it is necessary to develop a new high-capacity negative electrode system with a relative electrode potential lower than graphite (<0.1V) and a capacity density much higher than graphite (>800mAh / g).

[0003] According to the current research results of the industry and scientific research community, high-capacity silicon-based, phosphorus-based, and lithium metal-based negative electrode materials and corresponding battery systems have the greatest development potential. Among all the candidates, lithium metal negative electrode materials have the lowest electrode potential (-3.04Vvs.SHE) and the highest capacity density (3860mAh / g), and at the same time, new battery systems such as lithium sulfur and lithium air are expected to achieve an energy density of more than 600Wh / kg, showing great application prospects. Therefore, it has become one of the main directions of research and development of high-capacity negative electrode materials.

[0004] However, in order to achieve lithium metal anodes that can meet commercial applications and corresponding high energy density lithium metal battery systems, many challenges still need to be overcome:

[0005] First, the mechanical stability of lithium metal foil is poor, with insufficient tensile strength (1.5Mpa) and low strength (4.9Gpa). Therefore, in the process of forming pure metal lithium strips / foils, excessive thinning (<100μm) may lead to burrs, sickle bends, and severe processing stress cracks inside the lithium metal. In the process of forming and assembling lithium metal-based batteries, the electrical contact reliability between the tabs and the lithium metal negative electrode is also relatively poor, which can easily lead to internal short circuits in the battery cell.

[0006] Secondly, the electrochemical reaction process of lithium metal negative electrode is accompanied by unrestricted deposition / dissolution of lithium metal, severe deformation stress and continuous irreversible reaction between active lithium metal and electrolyte, which, on the one hand, causes considerable stress damage to the structure of lithium negative electrode, and on the other hand, causes continuous irreversible loss of negative electrode capacity and serious instability of internal structure of battery, thus leading to rapid deterioration of battery performance.

[0007] Finally, due to their active chemical properties and strong reducibility, metallic lithium or lithium-containing alloy materials are prone to side reactions and deterioration in a humid atmosphere, and oxidation is also prone to occur during the smelting process of preparing lithium-containing alloy materials. These reactions will lead to the deactivation of elemental lithium in the negative electrode material. Therefore, when using lithium metal / alloy foil as a negative electrode for batteries, vacuum or inert atmosphere protection is usually required during material preparation, metal strip processing and battery assembly, so the multi-step material production process is accompanied by extremely high production costs.

[0008] To address the problems of low structural strength and active chemical properties of lithium metal, the most commonly used method in the industry is to compound metallic lithium with other high-strength conductive film materials (such as copper foil, porous carbon felt, etc.) or directly prepare lithium-containing alloy metal strips during the preparation of negative electrode materials, thereby enhancing the overall structural stability of the metal negative electrode and avoiding the damage to the structure of the lithium-containing metal strip caused by various stress environments during negative electrode forming, battery cell assembly and battery operation; and coating the lithium metal side of the lithium-containing metal strip with an artificial SEI film (solid electrolyte interface film) composed of a continuous inorganic salt or organic solid electrolyte, thereby passivating the metal surface to a certain extent and improving the stability of lithium metal in air and liquid electrolytes.

[0009] However, the current artificial SEI modification process on the surface of lithium-containing metal strips in the industry is too complicated and cumbersome: first, the raw materials of the lithium-containing metal strips need to be processed and thinned, and then the oxides and other impurities on the surface of the metal strips need to be removed. Finally, the surface of the lithium-containing metal strips is treated with modification methods such as electrochemical sacrificial film-forming process, heat treatment formation process, and vacuum coating process to form artificial SEI. Since the forming step and the surface modification SEI step of the lithium-containing metal strip are carried out separately, not only the production procedure is complicated, but also the demand for production equipment, special production environment, and energy consumption is increased, thereby increasing the production cost of the artificial SEI modified lithium-containing metal strips and reducing production efficiency. In addition, due to the limitations of the film-forming process conditions, the uniformity, continuity, and integrity of the artificial SEI coated on the surface of the lithium-containing metal strips by the existing process are not ideal, so the passivation and protection of the lithium-containing metal strips are not reliable enough.

[0010] In summary, in order to realize a low-cost, high-energy-density lithium metal battery system, there is an urgent need for a strategy that can quickly, continuously, low-cost, and low-energy thin the lithium-containing metal strip and realize artificial SEI modification on the lithium metal surface. In addition, the artificial SEI is required to achieve complete, continuous, and uniform coating of the lithium-containing metal strip. Summary of the invention

[0011] The technical problem to be solved by the present invention is to provide a method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification, a modified lithium-containing metal strip and its application in view of the deficiencies in the above-mentioned prior art. The present invention mainly includes a process for forming a continuous, uniform and dense lithium halide artificial SEI coating on one side of the lithium metal while cold rolling the lithium-containing metal strip, and the application of the lithium-containing metal strip modified by the surface artificial SEI as a negative electrode material in a lithium metal battery. The core of the scheme of the present invention is to coat a halogenated polymer film on the surface of the roller as a modified functional layer during the rolling and thinning process of the lithium-containing metal strip, and stimulate the instantaneous and uniform reaction between the active metal lithium surface and the halogenated polymer on the surface of the roller through the deformation energy of mechanical processing, so as to finally realize the rolling and thinning of the lithium-containing metal strip and form a complete, dense and uniform lithium halide-dominated artificial SEI on the lithium metal side, thereby completing the thinning and forming process and artificial SEI coating of the lithium-containing metal strip at the same time. As a result, the process cost of lithium metal negative electrode molding is reduced and production efficiency is improved, while the performance of lithium-copper composite belt negative electrode is optimized. In addition, the strategy of the present invention can be extended to other metal negative electrodes and lithium-free negative electrodes and other material systems.

[0012] To achieve the above object, the technical solution adopted by the present invention is: In a first aspect of the present invention, a method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification is provided, comprising the following steps:

[0013] S1, coating the surface of a roller used for rolling a lithium-containing metal strip with a halogenated polymer film to obtain a roller having a halogenated polymer coating layer;

[0014] S2. The lithium-containing surface of the lithium-containing metal strip is rolled using a roller having a halogenated polymer film coating layer, and while thinning the lithium-containing metal strip, an artificial SEI coating layer is formed on the surface of the lithium-containing metal strip through a SEI film-forming reaction between the halogenated polymer film coating layer and lithium metal.

[0015] Preferably, the halogenated polymer film is a film made of an organic polymer compound containing any one or more of the four halogen atoms of fluorine, chlorine, bromine and iodine.

[0016] Preferably, the number average molecular weight of the organic polymer compound is 1000-10000000; the tensile strength of the halogenated polymer film is 1-1000 MPa, the Young's modulus is 0.1-100 GPa, and the thickness of the halogenated polymer coating layer is 0.01-10 mm.

[0017] Preferably, the lithium-containing metal belt is selected from any one of a pure lithium metal belt, a binary or multinary alloy belt of lithium and any other metal, a lithium-copper composite belt, and a lithium-carbon composite belt;

[0018] The metallic lithium or lithium alloy is distributed on at least one side of the lithium-containing metal strip. The lithium-containing metal strip has a thickness of 1 to 100 μm and a lithium content of 1 to 100%.

[0019] Preferably, in step S2, the rolling process is as follows:

[0020] The processing stress is 1-100 MPa, the single rolling reduction is 0.01-1 mm, the roller linear speed is 0.1-100 cm / s, the processing process is a combination of rough rolling and finish rolling, and the total rolling passes are 2-10 times.

[0021] Preferably, the halogenated polymer membrane is a polytetrafluoroethylene membrane, the number average molecular weight of the polytetrafluoroethylene raw material in the polytetrafluoroethylene membrane is 100,000 to 800,000, the tensile strength of the PTFE membrane is 10 to 30 MPa, and the Young's modulus is 1 to 20 Gpa;

[0022] The thickness of the halogenated polymer coating layer obtained by coating with the polytetrafluoroethylene film is 0.1 to 1 mm.

[0023] Preferably, the lithium-containing metal strip is a lithium-copper composite strip with a thickness of 30 to 90 μm, wherein the thickness of the copper layer is 5 to 10 μm, and the surface loading of the metal lithium is 4 to 18 mAh / cm 2 .

[0024] Preferably, the method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification comprises the following steps:

[0025] S1. Coating a polytetrafluoroethylene film on the surface of a roller used for rolling a lithium-containing metal strip to obtain a roller having a polytetrafluoroethylene coating layer with a thickness of 0.1 to 1 mm;

[0026] S2, cold rolling the lithium-containing surface of the lithium-copper composite strip using a roller having a polytetrafluoroethylene coating layer to form an artificial SEI coating layer on the surface of the lithium-copper composite strip;

[0027] Among them, the cold rolling processing technology is: the relative humidity of the processing environment is 0-15%, the rolling passes are 1-3 times, the rolling process is continuous 4H finishing rolling, the absolute reduction of the first rolling is 1-10μm, the absolute reduction of the subsequent rolling is 0.1-2μm, and the roller winding speed is 1-10cm / s.

[0028] The second aspect of the present invention provides a modified lithium-containing metal strip, which is prepared by the method as described above.

[0029] A third aspect of the present invention provides a use of the modified lithium-containing metal strip as described above as a negative electrode material in a lithium metal primary / secondary battery.

[0030] The beneficial effects of the present invention are:

[0031] 1. The present invention provides a method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification, a modified lithium-containing metal strip, and the use of the modified lithium-containing metal strip as a negative electrode material in a lithium metal primary / secondary battery; the present invention utilizes the various characteristics of commercial halide polymers to propose a solution for simultaneously achieving thinning and forming of a lithium-containing metal strip and artificial SEI coating of the lithium metal side of the lithium-containing metal strip through a one-step processing process, and the solution can form a continuous, complete, and uniform layer of high-performance lithium halide main material on the lithium metal surface through an instantaneous film-forming reaction while the lithium-containing metal strip is being finely rolled and formed. Introducing artificial SEI; through this scheme, the problems of uneven structure and performance of artificial SEI in the traditional lithium-containing metal belt preparation and surface artificial SEI modification process, reduced yield and increased cost caused by step-by-step processing can be avoided; through the scheme proposed in the present invention, large-scale one-time processing and forming of flat lithium-containing metal belts with artificial SEI on the surface can be achieved, the product quality is high and the consistency is good, it is more suitable for the production of commercial battery electrode materials, and it is helpful to improve the performance consistency of commercial battery cells; in addition, the scheme of the present invention can also be extended to the forming and modification of low-lithium / lithium-free negative electrodes.

[0032] 2. When the lithium-containing metal strip prepared by the process of the present invention is used as the negative electrode of a lithium metal battery, the flat lithium metal substrate can induce a relatively uniform lithium metal deposition / extraction reaction, and the continuous, complete, and uniform lithium halide-dominated artificial SEI with high strength and high lithium ion conductivity can not only improve the surface stability of the negative electrode, but also promote uniform lithium metal deposition / extraction reaction. Thus, the performance of the lithium metal negative electrode can be improved and dendrites can be suppressed.

[0033] 3. Taking the fluorine-rich artificial SEI coated lithium-copper composite tape (R-LiF / Li-Cu) prepared according to the scheme of the present invention as an example, the half-cell based on the R-LiF / Li-Cu electrode can be used in an ether electrolyte system at 2 mA / cm 2 , 5h charge and discharge time to achieve more than 450h of stable charge and discharge while maintaining a flat negative electrode surface without dendrites. In sharp contrast, the half-cell sample based on ether electrolyte assembled by cold rolling and heat treatment of lithium-copper composite strip (H-LiF / Li-Cu) coated with fluorine-rich artificial SEI using existing processes showed drastic fluctuations in the voltage curve during the cycle of less than 200h, and obvious dendrites or powdering appeared on the negative electrode surface after cycling.

[0034] 4. Subsequently, in order to expand the application field of the present invention, for example, to apply it to the preparation and modification of low-lithium / lithium-free negative electrode materials, a low lithium loading (~0.2 mAh / cm 2) as raw materials, the solution of the present invention and the traditional spontaneous lithiation strategy were used to achieve fluorine-rich artificial SEI coating on the Li-Cu composite tape, which were named R-LiF / Li-Cu and S-LiF / Li-Cu respectively. The half-cell test results showed that the R-LiF / Li-Cu||Li half-cell had a charge transfer rate of 1 mA / cm 2 The current density and 3mAh / cm 2 After repeated charge and discharge cycles, the average coulombic efficiency can reach 98.66±0.40%, which is much better than the S-LiF / Li-Cu||Li half-cell (94.17±10.52%) in both value and stability. Then, the full cell was assembled with LFP and it was found that the capacity retention rate of the R-LiF / Li-Cu||LFP full cell reached 44.6% after 50 charge and discharge cycles, which is still significantly better than the S-LiF / Li-Cu||LFP full cell (13.5%). BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic flow chart of the method for simultaneous thinning and forming of the lithium-containing metal strip and SEI coating modification in Example 1;

[0036] Figure 2 The surface morphology scanning electron microscope photo and energy spectrum analysis of the modified lithium-containing metal strip (labeled as R-LiF / Li-Cu) prepared in Example 1;

[0037] Figure 3 The surface morphology scanning electron microscope photo and energy spectrum analysis of the control group (labeled as H-LiF / Li-Cu) of the dry-rolled + heat-treated chemically formed film-forming lithium fluoride artificial SEI coated lithium-copper composite belt prepared in Example 1;

[0038] Figure 4 The repeated charge and discharge voltage curve of the symmetrical half-cell with R-LiF / Li-Cu as the electrode prepared in Example 2;

[0039] Figure 5 The repeated charge and discharge voltage curve of the symmetrical half-cell with H-LiF / Li-Cu as electrodes prepared in Example 2;

[0040] Figure 6 The scanning electron microscope photographs of the surface morphology of the R-LiF / Li-Cu (left) and H-LiF / Li-Cu (right) electrodes after repeated charge and discharge cycles of the half-cell in Example 3;

[0041] Figure 7 Coulomb efficiency test curve of the low-lithium R-LiF / Li-Cu or S-LiF / Li-Cu prepared in Example 4 as the working electrode and the pure lithium foil as the reference electrode;

[0042] Figure 8Coulombic efficiency and discharge capacity curves of the R-LiF / Li-Cu||LFP full battery experimental group and the S-LiF / Li-Cu||LFP full battery repeated charge and discharge test prepared in Example 5. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0044] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0045] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0046] The present invention aims at the problem that the dry rolling forming and artificial SEI modification processes of lithium-containing metal strips in the current industry are complicated, costly and low in yield. The present invention proposes a scheme for simultaneously performing thinning forming and artificial SEI modification of lithium-containing metal strips, thereby obtaining a lithium-containing metal strip with a flat lithium metal surface and a lithium metal surface coated with a complete and uniform artificial SEI. When the lithium-containing metal strip is used as a negative electrode material for a lithium metal battery, a dendrite-free negative electrode with long-term stable charging and discharging can be achieved. In addition, the present scheme can also be used for the preparation and modification of some negative electrode materials with little lithium or no lithium.

[0047] Specifically, the present invention provides a method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification, comprising the following steps:

[0048] S1, coating the surface of a roller used for rolling a lithium-containing metal strip with a halogenated polymer film to obtain a roller having a halogenated polymer coating layer;

[0049] S2. The lithium-containing surface of the lithium-containing metal strip is rolled using a roller having a halogenated polymer film coating layer, and while thinning the lithium-containing metal strip, an artificial SEI coating layer is formed on the surface of the lithium-containing metal strip through a SEI film-forming reaction between the halogenated polymer film coating layer and lithium metal.

[0050] The halogenated polymer film coating serves as both a wear-resistant layer for processing equipment and a sacrificial agent for artificial SEI film formation on the surface of lithium metal. The process of the present invention adopts a cold rolling process during the processing of lithium-containing metal strips, and utilizes uniform processing stress to induce a uniform film-forming reaction between a large area of ​​the lithium metal surface and the halogenated polymer coating layer on the roller surface, thereby forming a continuous, uniform, and complete artificial SEI dominated by inorganic salts such as lithium halides on the surface of lithium metal.

[0051] In a preferred embodiment, the halogenated polymer film is a film made of an organic polymer compound containing any one or more of the four halogen atoms of fluorine, chlorine, bromine and iodine.

[0052] In a preferred embodiment, the number average molecular weight of the organic polymer compound is 1000-10000000, and it can form a uniform and continuous film and cover the surface of the roller; the halogenated polymer film has good mechanical properties, with a tensile strength of 1-1000Mpa, a Young's modulus of 0.1-100Gpa, and a thickness of the halogenated polymer coating layer of 0.01-10mm.

[0053] In a preferred embodiment, the lithium-containing metal belt is selected from any one of a pure lithium metal belt, a binary or multinary alloy belt of lithium and any other metal, a lithium-copper composite belt, and a lithium-carbon composite belt.

[0054] In step S1, a lithium-containing metal strip blank of appropriate size is selected as a raw material for subsequent processing. In a preferred embodiment, active metal lithium or lithium alloy is distributed on at least one side of the metal strip, and the thickness of the lithium-containing metal strip is 1 to 100 μm, and the lithium content is 1 to 100%. In a more preferred embodiment, the lithium-containing metal strip is a lithium-copper composite strip with a thickness of 30 to 90 μm, wherein the thickness of the copper layer is 5 to 10 μm, and the surface loading of the metal lithium is 4 to 18 mAh / cm 2 .

[0055] The thickness of the relatively low-strength lithium metal side of the lithium-containing metal strip is reduced by roller-rolling processing stress, and the mechanical stability of the entire composite strip is enhanced by the work hardening mechanism. The formation mechanism of the artificial SEI is to use the intense instantaneous stress and thermal effect during the rolling process to activate the halogen-containing functional groups of the halogenated polymer coating layer on the roller surface and the lithium atoms on the lithium metal side, promoting a uniform instantaneous reaction between the two, thereby forming a uniform, continuous, and complete artificial SEI with halogenated lithium salts as the main component on the lithium metal surface.

[0056] In a preferred embodiment, in step S2, the rolling process is as follows:

[0057] The processing stress is 1-100 MPa, the single rolling reduction is 0.01-1 mm, the roller linear speed is 0.1-100 cm / s, the processing process is a combination of rough rolling and finish rolling, and the total rolling passes are 2-10 times.

[0058] In a preferred embodiment, the halogenated polymer membrane is a polytetrafluoroethylene (PTFE) membrane, the number average molecular weight of the polytetrafluoroethylene raw material in the polytetrafluoroethylene membrane is 100,000 to 800,000, the tensile strength of the PTFE membrane is 10 to 30 MPa, and the Young's modulus is 1 to 20 Gpa.

[0059] In a preferred embodiment, the thickness of the halogenated polymer coating layer obtained by coating with the polytetrafluoroethylene film is 0.1 to 1 mm.

[0060] In a preferred embodiment, the method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification comprises the following steps:

[0061] S1. Coating a polytetrafluoroethylene film on the surface of a roller used for rolling a lithium-containing metal strip to obtain a roller having a polytetrafluoroethylene coating layer with a thickness of 0.1 to 1 mm;

[0062] In one embodiment, the preparation method of the lithium-copper composite strip is as follows: a lithium metal layer with a thickness of 1 to 2 μm (surface loading of 0.2 to 0.4 mAh / cm2) is coated on the surface of the copper foil by melting and scraping. 2 ) to obtain a lithium-copper composite belt, which is used as a raw material for a lithium-poor metal belt.

[0063] S2, cold rolling the lithium-containing surface of the lithium-copper composite strip using a roller having a polytetrafluoroethylene coating layer to form an artificial SEI coating layer on the surface of the lithium-copper composite strip;

[0064] Among them, the cold rolling processing technology is: the relative humidity of the processing environment is 0-15%, the rolling passes are 1-3 times, the rolling process is continuous 4H finishing rolling, the absolute reduction of the first rolling is 1-10μm, the absolute reduction of the subsequent rolling is 0.1-2μm, and the roller winding speed is 1-10cm / s.

[0065] The present invention also provides a modified lithium-containing metal belt, which is prepared by the above method.

[0066] The present invention also provides a use of the modified lithium-containing metal strip as a negative electrode material in a lithium metal primary / secondary battery.

[0067] The present invention mainly utilizes the following advantages of halogenated polymer materials:

[0068] First, halogenated polymers usually have good wear resistance, high mechanical strength and reliable adhesion to traditional roll steel, so they can reliably cover the roll surface and prevent the adhesion between the roll metal and lithium metal during processing, thereby improving the surface processing quality of lithium-containing metal strips;

[0069] Secondly, the halogen atoms in the halogenated polymers usually have strong chemical activity. Therefore, under the stress of rolling processing, they can react with the active lithium metal surface of the lithium-containing metal strip to generate a lithium halide-rich inorganic salt layer, which can directly serve as a high-performance artificial SEI modification layer for the lithium metal negative electrode.

[0070] Thus, when the halide polymer film is coated on the surface of the stainless steel roller, the polymer film can form a uniform and reliable connection with the surface of the stainless steel roller. Subsequently, during the rolling and thinning process of the lithium-containing metal strip, the halide polymer film-coated roller is in direct contact with the lithium metal side of the lithium-containing metal strip and is rolled, thereby triggering an instantaneous high deformation energy and thermal effect at the contact point between the roller and the lithium metal, thereby using the energy of metal deformation to induce a rapid and uniform artificial SEI film-forming reaction between the halogenated polymer and the lithium metal while processing the lithium metal. Since the above-mentioned film-forming reaction and rolling processing behavior are carried out simultaneously, the thinning processing and forming of the lithium-containing metal strip and the modification of the artificial SEI rich in lithium halide can be achieved through a one-step process, thereby realizing the efficient and low-cost production of artificial SEI-modified lithium-containing metal strip materials.

[0071] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0072] Example 1

[0073] A method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification, comprising the following steps:

[0074] A 1 mm thick polytetrafluoroethylene (PTFE) film was coated on the surface of a 4H finishing roller. A 80 μm thick lithium-copper composite strip was used as a raw material. In an environment with a relative humidity of 5%, the lithium-copper composite strip was finish-rolled once with an absolute reduction of 8 μm using a PTFE-coated 4H finishing roller. Subsequently, the lithium-copper composite strip was finish-rolled again with an absolute reduction of 1 μm using a PTFE-coated 4H finishing roller. Figure 1 ), and finally a lithium-copper composite belt R-LiF / Li-Cu with a smooth surface and coated with lithium fluoride artificial SEI, that is, a modified lithium-containing metal belt, was obtained.

[0075] Using scanning electron microscopy and energy spectrum to analyze the surface morphology and composition, it can be seen that the lithium metal surface of the lithium-copper composite belt is flat, and the energy spectrum shows that the signal of the fluorine element is evenly distributed on its surface, proving that a uniform fluorine-rich artificial SEI coating layer has been formed on the surface ( Figure 2 ).

[0076] As a control, the same rolling process was used, in an environment with 5% humidity, polyethylene was used as a separation membrane, and an uncoated 4H roller was used to perform two finish rollings of the 80μm thick lithium-copper composite belt with the same amount of reduction. Then, a 0.1M LiF FEC solution was coated on the lithium metal surface of the lithium-copper composite belt as a film-forming sacrificial agent, and a mild heat treatment was performed at 45°C for 24 hours to achieve fluorine-rich artificial SEI formation, thereby obtaining a H-LiF / Li-Cu control group (heat treatment film-forming process) coated with a conventional process. Subsequently, scanning electron microscopy and energy spectrum were still used for surface morphology and composition analysis. The results showed that the surface of the lithium-copper composite belt formed by the conventional process not only had relatively poor flatness, but also had relatively uneven distribution of fluorine elements, proving that conventional processing and artificial SEI formation could not achieve a flat lithium metal surface of the lithium-containing metal belt, and it was also difficult to ensure the uniformity and continuity of the artificial SEI coating ( Figure 3 ).

[0077] Example 2

[0078] The R-LiF / Li-Cu and H-LiF / Li-Cu prepared in Example 1 were punched and cut into discs with a diameter of 16 mm, and then matched with 40 μL of 1M LiTFSI / DOL+DME ether electrolyte (Suzhou Fosai Electrolyte Company, commercial lithium-sulfur battery ether electrolyte), and Celgard2400PP membrane was used as a separator to assemble CR2032 symmetrical half-cells. 2 The charge and discharge current density and charge and discharge time of 5h were repeated for charge and discharge tests, while the control group H-LiF / Li-Cu was 1mA / cm 2 The charge and discharge current density of the experimental group R-LiF / Li-Cu was 10mAh / cm 2 The voltage curve is kept flat under high capacity cycling conditions ( Figure 4 ), while the control group H-LiF / Li-Cu is 4mAh / cm 2 The voltage curve fluctuates violently under mild cycling conditions ( Figure 5 ), which proves the superiority of the lithium-copper composite strip prepared by the present invention compared with the traditional process.

[0079] Example 3

[0080] In order to explore the reasons for the difference in the cycle performance of fluorine-rich SEI-coated lithium-copper negative electrodes prepared by different processes, two groups of electrode samples, R-LiF / Li-Cu and H-LiF / Li-Cu, were observed by scanning electron microscopy. The results showed that the surface of R-LiF / Li-Cu maintained a relatively flat morphology after 450 hours under high cycle capacity conditions, without obvious dendritic tissue. This proves that the flat lithium-copper composite belt (R-LiF / Li-C) coated with uniform artificial SEI prepared by the solution of this patent can maintain a long-term stable cycle without dendrites under high-capacity charge and discharge conditions, while the lithium-copper composite belt (H-LiF / Li-Cu) negative electrode prepared by the traditional process of cold rolling + thermal formation of artificial SEI cannot avoid the generation of dendritic tissue during long-term charge and discharge cycles under relatively stable and mild conditions ( Figure 6 ).

[0081] Example 4

[0082] In order to expand the application field of the scheme of the present invention, such as lithium-free / low-lithium negative electrode materials, molten lithium is scraped on the surface of a smooth 10μm thick copper foil to control its thickness to 1-2μm, that is, the surface capacity of active metal lithium is 0.2-0.4mAh / g, which is used as the raw material of the low-lithium negative electrode, and then treated separately by a process similar to Example 1 to obtain two materials, R-LiF / Li-Cu and S-LiF / Li-Cu. Two types of materials are used as working electrodes, respectively, with pure lithium metal foil as the reference / counter electrode, and 40μL of 1MLiTFSI / DOL+DME ether electrolyte is still used, and celgard2400PP membrane is used as the diaphragm to assemble a CR2032 asymmetric half-cell. For the R-LiF / Li-Cu||Li experimental group, according to the charging voltage range of 0-0.2V, 1mA / cm 2 The charge and discharge current density is 3mAh / cm 2 The charge and discharge capacity of the S-LiF / Li-Cu||Li control group was tested for 100 repeated charge and discharge tests; while the S-LiF / Li-Cu||Li control group was tested with the same voltage range and cycle capacity, but at a milder charge and discharge current density of 0.5 mA / cm 2 50 charge and discharge cycles were performed. The results showed that ( Figure 7 ), the average coulombic efficiency of the R-LiF / Li-Cu||Li half-cell can reach 98.66±0.40%, and the coulombic efficiency value and stability are much better than those of the S-LiF / Li-Cu||Li half-cell (94.17±10.52%). It can be seen that the scheme of the present invention is significantly superior to the traditional molding-forming process in the preparation and modification of low-lithium negative electrode materials.

[0083] Example 5

[0084] In order to further verify the superiority of the scheme of the present invention, the low-lithium R-LiF / Li-Cu prepared by the present invention in Example 4 and the low-lithium S-LiF / Li-Cu prepared by the conventional molding-chemical formation process were used as negative electrodes, respectively, and matched with LFP positive electrode materials (active material surface loading 6-8 mg / cm 2 ), and still using 40μL of 1M LiTFSI / DOL+DME ether electrolyte, with celgard2400PP membrane as separator, assemble CR2032 full battery. Repeated charge and discharge according to the voltage curve 2.8-3.8V, 1C rate. The results show that the capacity retention rate of R-LiF / Li-Cu||LFP full battery reaches 44.6% after 50 charge and discharge cycles, which is still significantly better than 13.5% of S-LiF / Li-Cu||LFP full battery, which proves that the scheme of the present invention is also superior to the traditional process in the low-lithium negative electrode based battery.

[0085] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for simultaneous thinning and forming of a lithium-containing metal strip and SEI coating modification, characterized in that: The following steps are involved: S1, coating the surface of a roller used for rolling a lithium-containing metal strip with a halogenated polymer film to obtain a roller having a halogenated polymer coating layer; S2. The lithium-containing surface of the lithium-containing metal strip is rolled using a roller having a halogenated polymer film coating layer, and while thinning the lithium-containing metal strip, an artificial SEI coating layer is formed on the surface of the lithium-containing metal strip through a SEI film-forming reaction between the halogenated polymer film coating layer and lithium metal.

2. The method for simultaneous thinning and forming of lithium-containing metal strips and SEI coating modification according to claim 1, characterized in that: The halogenated polymer film is a film made of an organic polymer compound containing any one or more of the four halogen atoms of fluorine, chlorine, bromine and iodine.

3. The method for simultaneous thinning and forming of lithium-containing metal strips and SEI coating modification according to claim 2, characterized in that: The number average molecular weight of the organic polymer compound is 1000-10000000; the tensile strength of the halogenated polymer film is 1-1000Mpa, the Young's modulus is 0.1-100Gpa, and the thickness of the halogenated polymer coating layer is 0.01-10mm.

4. The method for simultaneous thinning and forming of lithium-containing metal strips and SEI coating modification according to claim 1, characterized in that: The lithium-containing metal belt is selected from any one of a pure lithium metal belt, a binary or multinary alloy belt of lithium and any other metal, a lithium-copper composite belt, and a lithium-carbon composite belt; The metallic lithium or lithium alloy is distributed on at least one side of the lithium-containing metal strip. The lithium-containing metal strip has a thickness of 1 to 100 μm and a lithium content of 1 to 100%.

5. The method for simultaneous thinning and forming of lithium-containing metal strips and SEI coating modification according to claim 1, characterized in that: In step S2, the rolling process is as follows: The processing stress is 1-100 MPa, the single rolling reduction is 0.01-1 mm, the roller linear speed is 0.1-100 cm / s, the processing process is a combination of rough rolling and finish rolling, and the total rolling passes are 2-10 times.

6. The method for simultaneous thinning and forming of lithium-containing metal strips and SEI coating modification according to claim 1, characterized in that: in, The halogenated polymer membrane is a polytetrafluoroethylene membrane, the number average molecular weight of the polytetrafluoroethylene raw material in the polytetrafluoroethylene membrane is 100,000 to 800,000, the tensile strength of the PTFE membrane is 10 to 30 MPa, and the Young's modulus is 1 to 20 Gpa; The thickness of the halogenated polymer coating layer obtained by coating with the polytetrafluoroethylene film is 0.1 to 1 mm.

7. The method for simultaneous thinning and forming of lithium-containing metal strips and SEI coating modification according to claim 6, characterized in that: The lithium-containing metal belt is a lithium-copper composite belt with a thickness of 30 to 90 μm, wherein the thickness of the copper layer is 5 to 10 μm, and the surface loading of the metal lithium is 4 to 18 mAh / cm 2 .

8. The method for simultaneous thinning and forming of lithium-containing metal strips and SEI coating modification according to claim 7, characterized in that: The following steps are involved: S1. Coating a polytetrafluoroethylene film on the surface of a roller used for rolling a lithium-containing metal strip to obtain a roller having a polytetrafluoroethylene coating layer with a thickness of 0.1 to 1 mm; S2, cold rolling the lithium-containing surface of the lithium-copper composite strip using a roller having a polytetrafluoroethylene coating layer to form an artificial SEI coating layer on the surface of the lithium-copper composite strip; Among them, the cold rolling processing technology is: the relative humidity of the processing environment is 0-15%, the rolling passes are 1-3 times, the rolling process is continuous 4H finishing rolling, the absolute reduction of the first rolling is 1-10μm, the absolute reduction of the subsequent rolling is 0.1-2μm, and the roller winding speed is 1-10cm / s.

9. A modified lithium-containing metal strip, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. Use of the modified lithium-containing metal strip as claimed in claim 9 as a negative electrode material in a lithium metal primary / secondary battery.